Three-ring circus : Kobe, Shaq, Phil, and the crazy years of the Lakers dynasty - Pearlman, Jeff (Houghton Mifflin Harcourt, 2020)
"The story of the Lakers dynasty from 1996 through 2004, when Kobe Bryant and Shaquille O'Neal combined-and collided-to help bring the Lakers three straight championships and restore the franchise as a powerhouse"--